Online international learning: Internationalising the curriculum through virtual mobility at Coventry University. (2nd July 2016) - Villar-Onrubia, Daniel; Rajpal, Brinder
Abstract : Virtual mobility initiatives are one of the most flexible, versatile and inclusive approaches in the provision of international experience opportunities. Given that in most universities only a small fraction of students can benefit from forms of academic mobility that involve travelling abroad, Internet-based intercultural interactions prove to be instrumental in widening participation in international experience. This article focuses on the virtual mobility scheme of Coventry University (CU), known as Online International Learning (OIL). OIL projects involve online interactions between CU students and peers at non-UK universities, so they can work together on subject-specific learning tasks or activities while developing key attributes of global graduates, namely Intercultural Competence and Digital Skills. After discussing OIL within a wider Model for Progression in International Experience and outlining the role of virtual mobility in Internationalisation at Home initiatives, the article identifies core actors, types of interactions, policies, enablers, barriers, resource flows, technologies and other important considerations.